Alibaba's IT platform and electronic commerce synergy in driving "Singles' Day". Issue 3 (2nd July 2016) - Wu, Jen-Her; Li, Qi; Kee Wei, Kwok
Abstract: Global electronic commerce (ecommerce) development is growing exponentially, especially in the business-to-consumer (B2C) field. Consumers in the Asia-Pacific region have spent more on ecommerce purchases in 2014 than consumers in North America, making them the largest regional ecommerce market in the world. Singles' Day on November 11 (also known as Double 11 Day or Chinese National Ecommerce Day) is the most successful online shopping day in China. What drives the success of Singles' Day? We conducted in-depth interviews with Alibaba senior managers, observed the progress of Singles' Day, and investigated this issue. We find that over the past six years, Alibaba has successfully implemented five critical strategies associated with value activities from identifying merchants and pricing, marketing and sales, payments, and outbound logistics. Along with these strategies, Alibaba has created a synergistic IT platform to connect consumers, merchants, and service providers through identifying merchants and pricing, marketing and sales, payments, and outbound logistics to facilitate value creation by increasing efficiency in their value activities and expanding the market base. These successes have driven the interest of Chinese consumers to its annual shopping carnival on Singles' Day, changing consumer shopping from traditional stores to online sites and creating the miracle of the Chinese National Ecommerce Day.